Oral-Gut-Brain Axis in Experimental Models of Periodontitis: Associating Gut Dysbiosis With Neurodegenerative Diseases - Sansores-España, Luis Daniel; Melgar-Rodríguez, Samanta; Olivares-Sagredo, Katherine; Cafferata, Emilio A.; Martínez-Aguilar, Víctor Manuel; Vernal, Rolando; Paula-Lima, Andrea Cristina; Díaz-Zúñiga, Jaime (Frontiers in Aging, 2021)
Periodontitis is considered a non-communicable chronic disease caused by a dysbiotic microbiota, which generates a low-grade systemic inflammation that chronically damages the organism. Several studies have associated periodontitis with other chronic non-communicable diseases, such as cardiovascular or neurodegenerative diseases. Besides, the oral bacteria considered a keystone pathogen, Porphyromonas gingivalis, has been detected in the hippocampus and brain cortex. Likewise, gut microbiota dysbiosis triggers a low-grade systemic inflammation, which also favors the risk for both cardiovascular and neurodegenerative diseases. Recently, the existence of an axis of Oral-Gut communication has been proposed, whose possible involvement in the development of neurodegenerative diseases has not been uncovered yet. The present review aims to compile evidence that the dysbiosis of the oral microbiota triggers changes in the gut microbiota, which creates a higher predisposition for the development of neuroinflammatory or neurodegenerative diseases.The Oral-Gut-Brain axis could be defined based on anatomical communications, where the mouth and the intestine are in constant communication. The oral-brain axis is mainly established from the trigeminal nerve and the gut-brain axis from the vagus nerve. The oral-gut communication is defined from an anatomical relation and the constant swallowing of oral bacteria. The gut-brain communication is more complex and due to bacteria-cells, immune and nervous system interactions. Thus, the gut-brain and oral-brain axis are in a bi-directional relationship. Through the qualitative analysis of the selected papers, we conclude that experimental periodontitis could produce both neurodegenerative pathologies and intestinal dysbiosis, and that periodontitis is likely to induce both conditions simultaneously. The severity of the neurodegenerative disease could depend, at least in part, on the effects of periodontitis in the gut microbiota, which could strengthen the immune response and create an injurious inflammatory and dysbiotic cycle. Thus, dementias would have their onset in dysbiotic phenomena that affect the oral cavity or the intestine. The selected studies allow us to speculate that oral-gut-brain communication exists, and bacteria probably get to the brain via trigeminal and vagus nerves.